Interprète simultané par rapport à l’image - Woroch, Justyna (Studia Romanica Posnaniensia, 2021)
The aim of this article is to signal the possible relationships between the simultaneous interpreter and the image in its widest sense. In this communicative situation, attention is first paid to the text of the oral presentation, the meaning of which is conveyed by the interpreter. However, this meaning is also made up of visual elements that the interpreter faces and which make the interpretation inter-semiotic and multimodal. Three different types of simultaneous interpreter/image relationships will be outlined: firstly, the whole interpreting communicative situation can become an image if remote interpretation is necessary, secondly, it is the speaker who can be understood as an image, thirdly, the speaker can refer to previously prepared images. Then, by means of a pilot study, it will be checked whether and how experienced simultaneous interpreters relate the speaker to the picture when the picture presented is not redundant with what is being said, but complements the speech. The main question is whether and how it will be verbalized. Possible ways of extending the study will also be discussed.